PELAKSANAAN PIDANA TAMBAHAN PEMBAYARAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI DI KEJAKSAAN NEGERI KLUNGKUNG - Gunadi, I Komang Pasek (Kerta Dyatmika, 2024)
The Attorney General's Office, in addition to its authority in carrying out prosecutions, also has the authority as executor to carry out court decisions. The problem that occurs in the implementation of additional criminal payments for replacement money is that the return of state financial losses is not yet optimal related to the authority of the Attorney General's Office as an institution tasked with executing a court decision. Therefore, to find out the problems in the implementation of this additional sentence, this research will be conducted at the Klungkung State Prosecutor's Office as one of the State Prosecutors' Offices in the jurisdiction of the Province of Bali. As for the formulation of the first problem, How is the implementation of additional criminal payment of replacement money at the Klungkung District Attorney's Office and what are the obstacles in implementing additional criminal payment of replacement money at the Klungkung District Attorney's Office. This study includes empirical legal research, using the nature of explanatory research. The data sources consist of primary data sources, secondary data. The data collection technique used in this research is interviews. The data analysis used in this research is qualitative analysis. Based on the results of the research that has been reviewed and described, the conclusions that can be conveyed are as follows, The implementation of additional punishment for payment of replacement money has not been perfect, so that the purpose of this additional punishment has not been optimally achieved. And second, obstacles in the implementation of the additional penalty for payment of replacement money at the Klungkung District Attorney, namely the existing legal regulations have not fully supported efforts to implement this additional penalty.